Announcement-specific decompositions of unconventional monetary policy shocks and their macroeconomic effects - Daniel J. Lewis (Federal Reserve Bank of New York, 2019)
I propose to identify announcement-specific decompositions of asset price changes into monetary policy shocks based on intraday time-varying volatility. This approach is the first to accommodate changes in both the nature of shocks and the state of the economy across announcements. I compute daily historical decompositions with respect to three monetary policy shocks for the United States from 2007 to 2018. I derive expressions for the asymptotic variance of such historical decompositions and apply them to assess the statistical significance of notable announcements. Only a handful spark significant shocks, and I discuss the characteristics of those announcements in detail. For many announcements, asset purchase shocks lower corporate borrowing costs, but spreads increase in response to both asset purchases and forward guidance. Turning to the real economy, I find that the asset purchase shock has significant effects on consumer and professional expectations of inflation and GDP growth. I compute dynamic responses of inflation and GDP growth; asset purchases have significant expansionary effects, while fed funds shocks and forward guidance do not.
Keywords: C32; C58; E44; E52; E58; 330; high-frequency identification; time-varying volatility; monetary policy shocks; forward guidance; quantitative easing